Investigating the role of verbal cues on learning of tool-use actions in 18- and 24-month-olds in an online looking time experiment - Trouillet, Léonie; Bothe, Ricarda; Mani, Nivedita; Elsner, Birgit (Frontiers in Developmental Psychology, 2024)
This study was an unmoderated online experiment to investigate the impact of the semantic content of verbal cues on toddlers' action learning. 18-and 24-month-olds (N=89) watched videos of two tool-use actions accompanied by specific ("pressing in/pulling out") or unspecific information ("doing that"). Learning was measured via looking times coded from webcam recordings. Regardless of age and verbal cue, toddlers looked equally long to test pictures of correct or incorrect tool-use, suggesting that meaningful verbal information did not improve the challenging video-based action learning. However, low drop-out rates and high webcam data quality confirm the feasibility of online experiments with toddlers.